Plasma VEGF and Leptin Values in Patients With Gastric Intestinal Metaplasia and Metabolic Syndrome - Pappas-Gogos, George; Tepelenis, Kostas; Goussia, Anna; Tellis, Constantinos; Fousekis, Fotis; Glantzounis, Georgios K.; Vlachos, Konstantinos (Frontiers in Oncology, 2022)
Intestinal metaplasia of the stomach (IM) is considered a pre-cancerous lesion and is a potential precursor to adenocarcinoma. Metabolic syndrome (MetS) has been associated with lesions to the gastrointestinal tract such as the risk of developing Barett esophagus. Vascular endothelial growth factor and leptin have been associated with either gastrointestinal tract carcinogenesis or MetS. In this context, this study was designed to analyze plasma levels of VEGF and leptin in patients with IM and MetS. Four groups of 137 participants (a control group and three patient groups, IM, MetS and IM- MetS) were created. Inclusion criteria for the presence of IM were endoscopic findings and histological confirmation, while for MetS the ATP III and IDF guidelines. Levels of plasma vascular endothelial growth factor (VEGF) and leptin (Leptin) were determined. VEGF levels were increased in IM (IM vs Control, p=0,011) and IM-MetS groups (IM-MetS vs Control, p <0.001 and IM-MetS vs MetS, p=0.001). Leptin levels were found to be increased in the MetS group (MetS vs. Control, p <0.001 and MetS vs IM, p <0.001) and in IM-MetS (IM-MetS vs Control, p = 0.002, IM-MetS vs IM, p=0.033). Patients with intestinal metaplasia and metabolic syndrome (I M - Me t S g r o u p) have elevated levels of VEGF, while leptin levels were associated predominantly with MetS and not with IM.